Assessing the productivity of Serbian manufacturing industry with Malmquist DEA indices - Nikolić, Ivan; Miljković, Marko (Industrija, 2024)
The subject of this paper is the productivity of the manufacturing industry of Serbia. The analysis was conducted on data for 85 manufacturing groups of Serbian industry during the period 2012-2022. Changes in total factor productivity, as well as the decomposition of these changes into technological changes and innovations on the one hand, and efficiency changes on the other, were estimated using Malmquist indices calculated by DEA program. The introduction offers a brief overview of the macroeconomic context in which industrial production takes place. The second chapter is devoted to the methodology and the presentation of the data used. In the third part of the paper, the results of the research are presented. The total factor productivity of the manufacturing industry grew at a low average rate of about 0.5% annually. The manufacturing industry lacks continuity of growth, with no more than two years of consecutive productivity growth recorded. The best results were achieved in the manufacture of coke and refined petroleum products, electrical equipment and other transport equipment. Productivity growth in these divisions is rather the result of efficiency improvements than technological changes, i.e. innovations. The biggest decline was achieved in the manufacture of basic iron and steel.